Strategi Komunikasi Pemasaran Elite Pro Green Lake City Dalam Upaya Meningkatkan Penjualan Properti Tahun 2023 - Devi Julianti; Mad Yoman; Mochammad Mirza (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
An effective marketing strategy plays an important and diverse role in a company's operations. Understanding marketing strategies and their impact on business objectives is very important for companies. The research problem focused on ineffective marketing communication strategies that impacted property sales at Elite Pro Green Lake City. The purpose of this study is to explore the marketing communication strategies used by companies and their impact on property sales. This research adopts a constructivist paradigm and uses a qualitative approach with a descriptive research design. A case study method was used, with primary data collected from Creative Managers and Marketing Staff at Elite Pro Green Lake City. Secondary data from the literature and previous research provide additional support. The study was conducted at the company's location in Green Lake City, Tangerang. The study revealed that Green Lake City's Elite Pro has yet to fully optimize its marketing communication strategy. The company mainly focuses on the product, price, and promotional components of the marketing mix, neglecting other important elements. This resulted in a decrease in property sales. These findings point to the need for Elite Pro Green Lake City to improve its marketing communication strategy to increase property sales. The study underscores the importance of leveraging various online and offline promotional activities, developing strong relationships with develovers and banks, and maximizing social media platforms for marketing.